1987
DOI: 10.1037/0735-7028.18.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Consultation and counseling as procedurally divergent: Analysis of verbal behavior.

Abstract: We sought to demonstrate the procedural divergence of consultation and counseling techniques by analyzing the verbal behaviors of consultants and counselors. Sixty graduate students served as subjects. Half of them had been trained as counselors, and the other half had been trained in consultation. The two groups were matched for age, sex, and extent of training. Audiotapes and transcripts of consultation and counseling sessions were obtained for each subject and coded via the Counselor Verbal Behavior Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Many studies have addressed these kinds of questions by employing more conventional approaches based in the scientific method (e.g., Curtis & Watson, 1980;Graden, Casey, & Bronstrom, 1985;Gutkin & Ajchenbaum, 1984;Gutkin & Bossard, 1984; Henning-Stout & J. C. Conoley, 1987;Pryzwansky & White, 1983;Witt & Elliott, 1983;Witt, Moe, Gutkin, & Andrews, 1984). The findings of these studies have provided interesting and important insights into possible patterns in successful and unsuccessful consultation.…”
Section: Connected Knowing and Consultation Researchmentioning
confidence: 95%
“…Many studies have addressed these kinds of questions by employing more conventional approaches based in the scientific method (e.g., Curtis & Watson, 1980;Graden, Casey, & Bronstrom, 1985;Gutkin & Ajchenbaum, 1984;Gutkin & Bossard, 1984; Henning-Stout & J. C. Conoley, 1987;Pryzwansky & White, 1983;Witt & Elliott, 1983;Witt, Moe, Gutkin, & Andrews, 1984). The findings of these studies have provided interesting and important insights into possible patterns in successful and unsuccessful consultation.…”
Section: Connected Knowing and Consultation Researchmentioning
confidence: 95%
“…Being facilitative may mean that verbal techniques are not used in the same manner in consultation as they are in counseling. Henning-Stout and Conoley (1987) found that counselortrainees used more verbally restrictive leads (as opposed to open-ended) when they were engaged in consultation than when they were counseling. They concluded that their findings suggest that counseling and consultation are procedurally divergent interventions.…”
Section: Implications For Practitionersmentioning
confidence: 92%
“…While it is true that a few programs (about 14%) offer some training in consultation (Brown, Spano, & Schulte, 1988), it seems unlikely that counselor trainees receive the type of training they need, since the skills required are quite different from those required in counseling (see Bergan, 1977;Parsons & Meyers, 1984). Research also suggests that traditional counseling techniques may be employed quite differently in consultation than in counseling (Henning-Stout & Conoley, 1987). Therefore, counselor educators who genuinely wish to develop interpersonal skills that will ensure the likelihood of success in consultation are faced with reconceptualizing their training programs in this area.…”
Section: Implications For Counselor Educationmentioning
confidence: 99%
“…Consultants need to be taught a set of consulting skills that involve the use their basic human relations skills in the consulting process as well as some unique consulting skills. Nevertheless, there are studies that suggest that the consultant needs to be more direct, ask more questions, and be more actively engaged in diagnosing both the consultee's and client's problems (Bergan & Tombari, 1976;Erchul, 1987;Henning-Stout & Conoley, 1987). Nevertheless, there are studies that suggest that the consultant needs to be more direct, ask more questions, and be more actively engaged in diagnosing both the consultee's and client's problems (Bergan & Tombari, 1976;Erchul, 1987;Henning-Stout & Conoley, 1987).…”
Section: Behavioral Skillsmentioning
confidence: 99%
“…Counseling and consultation are to some degree procedurally divergent (Henning-Stout & Conoley, 1987). Consultants need to be taught a set of consulting skills that involve the use their basic human relations skills in the consulting process as well as some unique consulting skills.…”
Section: Behavioral Skillsmentioning
confidence: 99%